The Fair Allocation of Scarce Medical Resources: A Comparative Study From Jordan - Yousef, Muhannad H.; Alhalaseh, Yazan N.; Mansour, Razan; Sultan, Hala; Alnadi, Naseem; Maswadeh, Ahmad; Al-Sheble, Yasmeen M.; Sinokrot, Raghda; Ammar, Khawlah; Mansour, Asem; Al-Hussaini, Maysa (Frontiers in Medicine, 2021)
The allocation strategies during challenging situations among the different social groups is based on 9 principles which can be considered either individually: sickest first, waiting list, prognosis, youngest first, instrumental values, lottery, monetary contribution, reciprocity, and individual behavior, or in combination; youngest first and prognosis, for example. In this study, we aim to look into the most important prioritization principles amongst different groups in the Jordanian population, in order to facilitate the decision-making process for any potential medical crisis. We conducted an online survey that tackled how individuals would deal with three different scenarios of medical scarcity: (1) organ donation, (2) limited hospital beds during an influenza epidemic, and (3) allocation of novel therapeutics for lung cancer. In addition, a free-comment option was included at the end of the survey if respondents wished to contribute further. Seven hundred and fifty-four survey responses were gathered, including 372 males (49.3%), and 382 females (50.7%). Five groups of individuals were represented including religion scholars, physicians, medical students, allied health practitioners, and lay people. Of the five surveyed groups, four found “sickest-first” to be the most important prioritization principle in all three scenarios, and only the physicians group documented a disagreement. In the first scenario, physicians regarded “sickest-first” and “combined-criteria” to be of equal importance. In general, no differences were documented between the examined groups in comparison with lay people in the preference of options in all three scenarios; however, physicians were more likely to choose “combination” in both the second and third scenarios (OR 3.70, 95% CI 1.62-8.44, and 2.62, 95% CI 1.48-4.59; p < 0.01 ), and were less likely to choose “sickest-first” as the single most important prioritization principle (OR 0.57, CI 0.37-0.88, and 0.57; 95% CI 0.36-0.88; p < 0.01). Out of 100 free comments, 27 (27.0%) thought that the " social-value” of patients should also be considered, adding the 10th potential allocation principle. Our findings are concordant with literature in terms of allocating scarce medical resources. However, “social-value” appeared as an important principle that should be addressed when prioritizing scarce medical resources in Jordan. .